AN ANALYSIS OF FIGURATIVE LANGUAGE IN DISNEY MOVIE SONGS - Hariyani, Hardianti; Rosnija, Eni; Rahmani, Eka Fajar (Journal of English Language Teaching and Literature (JELTL), 2024)
The aimed of this study was to analyze the figurative language used in the Disney movie songs. The data were collected from the internet with five song titles selected from different Disney movies including; Lead the Way (Raya and the Last Dragon), Carried Me With You (Onward), Nobody Like U (Turning Red), Loyal Brave, and True (Mulan), and Part of Your World (The Little Mermaid). By utilizing descriptive qualitative as the research method, the researcher analyzed the interpretation of five types of figurative language including: metaphor, simile, personification, irony, and hyperbole. The findings in this study through analyzed the five songs indicated that there are 43 figurative languages, consists of 13 metaphors, 2 similes, 4 personifications, 3 ironies, and 21 hyperboles. It can be concluded that hyperbole was the dominant type of figurative in Disney song lyrics. Therefore, this study may help readers, especially for teachers and students in understand the analysis of figurative language theory songs.